2020
DOI: 10.1007/s00701-020-04485-5
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive analysis of low versus elevated intracranial pressure on cerebral physiology in adult traumatic brain injury: a CENTER-TBI exploratory study

Abstract: Background To date, the cerebral physiologic consequences of persistently elevated intracranial pressure (ICP) have been based on either low-resolution physiologic data or retrospective high-frequency data from single centers. The goal of this study was to provide a descriptive multi-center analysis of the cerebral physiologic consequences of ICP, comparing those with normal ICP to those with elevated ICP. Methods The Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury (CENTER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…In keeping with the literature, we know that in the face of high ICPs, we tend to see low CPPs (CPP = MAP–ICP), and it stands out as significant in this patient population. 22 , 46 Thus, the high ICP and low CPP values in our cohort were seen among the females who are younger instead of the older male patients, which is similar with a single study on sex-based analysis of high-frequency cerebral physiology in moderate/severe TBI. 19 Our results differ, however, because cerebrovascular reactivity metrics do not appear to be different between males versus females, as seen in this previous work.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In keeping with the literature, we know that in the face of high ICPs, we tend to see low CPPs (CPP = MAP–ICP), and it stands out as significant in this patient population. 22 , 46 Thus, the high ICP and low CPP values in our cohort were seen among the females who are younger instead of the older male patients, which is similar with a single study on sex-based analysis of high-frequency cerebral physiology in moderate/severe TBI. 19 Our results differ, however, because cerebrovascular reactivity metrics do not appear to be different between males versus females, as seen in this previous work.…”
Section: Discussionsupporting
confidence: 86%
“… 25 Finally, the data demonstrated that PRx insult burden was substantial over the course of the first few days of ICU stay and remained relatively independent to ongoing active treatment, which validates previous findings from the Collaborative European NeuroTrauma Effectiveness Research in TBI study. 12 , 46 Yet, aside from these promising findings, there were some additional findings of interest that deserve highlighting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are few studies in the literature examining the association between age/sex and PbtO 2 in moderate/severe TBI. Studies examined showed that older patients trended towards having lower PbtO 2 and tended to suffer undesirable outcomes ( Stiefel et al, 2005 ; Martini et al, 2009 ; Zeiler et al, 2020d ). Though, it must be acknowledged, that all of the identified relationships failed to reach statistical significance, and only showed a potential relationship based on raw differences in mean/median magnitudes.…”
Section: Standard Monitoring In Traumatic Brain Injurymentioning
confidence: 99%